Strategies to Govern Children and Underprivileged Youth in Brazil (1865-1905) (2017)
In this article, strategies to govern children and underprivileged youth are discussed through the analysis of two public institutions for the protection and the professionalization of this social group. State presence in the organization and the maintenance of the Companhia de Aprendizes Marinheiros de Sergipe —Company of Trainee Seaman in Sergipe— and in the Asilo de Meninos Desvalidos —Home for Destitute Children— located in the city of Rio de Janeiro was taken as a point of reference. In this sense, the emergence of the public assistance-based approach and its practices are highlighted and, consequently, also the role of the State in the education of poor children at the military barracks as well as in the preparation for a particular job in different sectors of society. In order to facilitate the research, a set of documents was gathered including reports of Ministers, rules and regulations of the institutions concerned. The research is based on the notions of civilization and protecting / welfare state. The analysis of the intersection that exists between these two institutions allowed us to understand the heterogeneity of a particular way of organizing the assistance for the professionalization, in other words, civilian and military institutions having acquired functions of refuge and professional education, in addition to regular education.